Evaluation of Sapta Pesona Aspects in the Management of Religious Tourism: Ketaq Tomb, Central Lombok Regency - Muhammad Amar; Fathurrahim; Uwi Martayadi (Jurnal Pariwisata Nusantara (JUWITA), 2022)
Purpose: this study aims to describe the management of the Ketaq Tomb in the perspective of Sapta Pesona and to find out the supporting and inhibiting factors in its management. Methods: In this study, the data collection process was carried out by observation, interviews, and documentation. While the analysis process involves several techniques, including data reduction, data display, drawing conclusions, and triangulation. Results: This study found that the management of the Ketaq Tomb is still not optimal, especially regarding supervision from the Regional Government. Meanwhile, the management in the perspective of Sapta Pesona has not been fully implemented, especially the orderly and clean elements of the Ketaq Tomb area. Many tourists and organized human resources are supporting factors for tourism activities. Meanwhile, conflict of heirs, road access, inadequate parking space, weak coordination and cooperation with local governments are the main problems. Contribution: This study provides a description of implementing Sapta Pesona in Monggas Village, Kopang District, Central Lombok Regency.